Cookie - Wilson, Jacqueline; Sharratt, Nick (London : Corgi, 2008)
Plain and timid Beauty Cookson is teased by popular girls at school, but even worse are the unrelenting criticism and rage from her bad-tempered father, until the day her sweet mother discovers a way out.
Keywords: Baking -- Fiction; Family problems -- Fiction; Schools -- Fiction; Self-esteem -- Fiction; Teasing -- Fiction